47 #InfluenceMe: an investigation into social media health influencers and the impact they have on their followers. (3rd November 2019) - Ayorinde, Ayomide; Compton, Alex; Liu, Chen; Ludley, Alistair; Patel, Nikisha; Rose, Joseph; Shaikh, Faiz
Abstract : Social Media Health Influencers (SMHIs) can be defined at the most basic level as those who influence their followers' perspectives by posting online health-related content. SMHI followers are individuals who watch, take advice from or subscribe to an SMHI. This study aimed to investigate SMHIs' effect on their followers and explore the responsibilities of SMHIs in the online space and their capacity to enhance health education. Primary data collection involved surveying individuals to understand the effect of SMHIs. Furthermore, the research team launched the National Collaborative for Health and Social Media (NCHSM), which aims to facilitate future research and raise awareness about issues surrounding social media and health. The NCHSM hosted '#InfluenceMe: The Responsibility of Online Social Power in Wellbeing', where a panel of SMHIs discussed the challenges of operating responsibly on social media. Of the sample surveyed (n=206), 68 participants were identified as SMHI followers. 63% of SMHI followers reported changing a decision or action due to SMHIs, suggesting SMHIs may influence followers' health-related decisions or actions. Key differences between followers that changed behaviours based on SMHI advice and those that did not, included the number of SMHIs followed and how often health content was viewed. Followers were also keen for healthcare organisations to use SMHIs in health education. However, the #InfluenceMe event suggested that healthcare leaders (e.g. senior Healthcare Professionals) are needed to verify SMHIs and ensure their social media content is accurate. SMHIs appear to have an impact on their followers' behaviours. In order to elicit positive behaviour changes in followers, SMHIs must create accurate content and act responsibly online. Healthcare leaders have the potential to verify SMHIs so that their involvement in health education is optimal. Healthcare leaders themselves also have potential to act as SMHIs in today's digital age.